Principles of the Economic Analysis and Criteria for Evaluation of Corporate Structures Functioning - Pugacheva, M.A.; Girfanova, E. Ju.; Pugacheva, S.D.; Nuriyahmetova, S.M. (International Journal of Criminology and Sociology, 2022)
In this article, authors attempt to investigate and specify the principles of the economic analysis and criteria for evaluation of activity of corporate structures in the conditions of instability of the external environment that allowed defining degree of completeness of their realization in practice. For receiving quality and objective standard of the economic analysis results, in the course of its carrying out we seek to consider the established principles representing the set of rules. Based on the outcomes, it can be concluded that the possibility of their full realization in many respects depends on institutional, legal and infrastructure conditions, professionalism of management of that region in the territory of which the corporation is located. Need of introduction of the principles of adaptability, relevance, independence, clarity and openness of results of the economic analysis is proved.